INOVASI, MASALAH, DAN TANTANGAN DALAM PENYUSUNAN RDTR UNTUK OSS - Eko Budi Santoso; Aulia Iswi; Ipung Yanuasmara (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2020)
This paper is the result of the author's study of his involvement in the preparation of the Eastern Sendawar Spatial Detail Plan (RDTR) in West Kutai Regency, East Kalimantan Province. Although the author's study is based on one case directly involved, but from sharing between planners the fact is that the various problems that occur are relatively similar to the various cases of the preparation of RDTR in other regions in Indonesia prepared for input of Online Single Submission (OSS), which began to be officially applied as of January 1, 2020. The results of this study, although they cannot be generalized, can be used as lesson learnt in the preparation of other RDTRs for the same type of RDTR and other regular RDTRs that have relatively similar characteristics. The results of the study indicate that there are still some weaknesses that need to be addressed both in the guidelines, standards, and synchronization with the system in OSS. It is recommended to do crash program preparing the base maps and related thematic maps, ajusment/improvement the guidelines, separate processes with KLHS, and prepare human resources for managing flexible systems on OSS